Structural and histochemical aspects of the Gymnotus carapo tegument (Teleostei: Gymnotiformes) - Blanco Cohene, Tania Katherina (2023)
The present study aims to structurally and histochemically characterize the Gymnotus carapo tegument. 30 specimens were captured and slaughtered by spinal section with anesthesia. The observation was carried out with a stereoscopic microscope and the body surface was photographed. Fragments of the dorsal, ventral and lateral region were fixed in Bouin’s solution for 12 hours and subsequently preserved in 70% alcohol. They were subsequently observed in the scanning electron microscope (SEM). The preparation for SEM was performed following the standardized protocol. Histological preparations were made, and the cuts were colored with H-E, PAS and Coomassie Blue. The images were obtained in an Olympus BX41-ENUTV-4 microscope. From the observations in SEM a plain tegument with pores of different sizes could be evidenced. The scales of the different regions of the body have different ornaments. Microscopically it was composed of a stratified non-keratinized epithelium consisting of two types of morphologically distinct cells: epidermal cells and mucous cells (PAS-Commassie Blue positive). Under the epithelium there is a layer of dense irregular connective tissue with associated chromatophores and more deeply scales. These analyzes are the basis for future studies that will focus on elucidating the events related to integumentary healing in this species.